2018
DOI: 10.1152/ajprenal.00065.2018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lithium treatment induces novel patterns of pendrin localization and expression

Abstract: Prolonged lithium treatment is associated with various renal side effects and is known to induce inner medullary collecting duct (IMCD) remodeling. In animals treated with lithium, the fraction of intercalated cells (ICs), which are responsible for acid-base homeostasis, increases compared with renal principal cells (PCs). To investigate the intricacies of lithium-induced IMCD remodeling, male Sprague-Dawley rats were fed a lithium-enriched diet for 0,1, 2, 3, 6, 9, or 12 wk. Urine osmolality was decreased at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…9 This is supported by observations of novel cell types in the CD displaying both intercalated and principal cell markers after Li-treatment and recovery. 10,42 In addition, both Type A and Type B intercalated cells have previously been demonstrated to be derived from AQP2-positive cells in the developing kidney. 43 The loss of basal labeling and cellular detachment could potentially occur during a transition from one cell type to another.…”
Section: E-cadherin and β-Catenin Are Both Absent In Primarily Princi...mentioning
confidence: 99%
“…9 This is supported by observations of novel cell types in the CD displaying both intercalated and principal cell markers after Li-treatment and recovery. 10,42 In addition, both Type A and Type B intercalated cells have previously been demonstrated to be derived from AQP2-positive cells in the developing kidney. 43 The loss of basal labeling and cellular detachment could potentially occur during a transition from one cell type to another.…”
Section: E-cadherin and β-Catenin Are Both Absent In Primarily Princi...mentioning
confidence: 99%
“…Long‐term exposure to lithium has been demonstrated to induce remodeling of the CDs, particularly in the inner medulla, characterized by the presence of pendrin‐positive cells. [ 27 ] Therefore, we assessed pendrin expression across various renal segments to determine whether low‐dose exposure altered its expression pattern. Consistent with prior findings, we observed that pendrin expression was markedly higher in the cortex compared to the deepest segments, by at least a five‐fold increase [ 28 ] (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there were no significant variations observed within each segment between control and lithium‐treated rats, in contrast to the findings reported by Himmel et al, who administered a high dose of lithium. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney biopsy samples from patients receiving lithium show diffuse tubulointerstitial nephritis 134 but whether this inflammation could cause dRTA is unclear and no studies have specifically examined intercalated cells. In a rat model of chronic lithium ingestion, increased pendrin expression and aberrant pendrin localization were observed in the inner medulla 135 . Hypothetically, increased pendrin activity could mediate inappropriate bicarbonate secretion into urine, resulting in renal acidosis similar to that seen in a mouse model of pseudohypoldosteronism type II (PHAII) with elevated pendrin activity 136 .…”
Section: [H2] Drugs and Toxinsmentioning
confidence: 98%